ICRISAT Sahelian centre opens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
General Ali Saibou, Niger's head of state, opened the US$250million ICRISAT Sahelian Centre in March 1989. It is a major research complex for the improvement of agriculture in the semi-arid region of West Africa, and covers some 500ha at Sadore,...